1998
DOI: 10.1038/35826
|View full text |Cite
|
Sign up to set email alerts
|

DNA-templated assembly and electrode attachment of a conducting silver wire

Abstract: Recent research in the field of nanometre-scale electronics has focused on two fundamental issues: the operating principles of small-scale devices, and schemes that lead to their realization and eventual integration into useful circuits. Experimental studies on molecular to submicrometre quantum dots and on the electrical transport in carbon nanotubes have confirmed theoretical predictions of an increasing role for charging effects as the device size diminishes. Nevertheless, the construction of nanometre-scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
1,800
3
29

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,309 publications
(1,851 citation statements)
references
References 25 publications
19
1,800
3
29
Order By: Relevance
“…As can be seen, the initial I-V sweep (cycle 1) is not ohmic; rather, there are symmetric current plateaus centered around zero voltage, indicative of electron-tunneling barriers probably at the grain boundaries and the specimen/electrode contact. 8,33 Because these nanowires were generated by overcoating gold nanoparticle seeds through multiple electroless silver plating steps, there are many grain boundaries (visible using both SEM and TEM) and this behavior is not surprising based on hopping conduction through many metallic domains. Cycling the device reduced these effects until almost purely ohmic behaviour was observed after 15 cycles of I-V scans.…”
Section: Electronic Properties Of Metallic Collagen Nanowiresmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen, the initial I-V sweep (cycle 1) is not ohmic; rather, there are symmetric current plateaus centered around zero voltage, indicative of electron-tunneling barriers probably at the grain boundaries and the specimen/electrode contact. 8,33 Because these nanowires were generated by overcoating gold nanoparticle seeds through multiple electroless silver plating steps, there are many grain boundaries (visible using both SEM and TEM) and this behavior is not surprising based on hopping conduction through many metallic domains. Cycling the device reduced these effects until almost purely ohmic behaviour was observed after 15 cycles of I-V scans.…”
Section: Electronic Properties Of Metallic Collagen Nanowiresmentioning
confidence: 99%
“…4a the resistivity was estimated to be 4 × 10 −5 Ωm which is considerably higher than that expected for polycrystalline silver 33 but on par with previous reports of biomolecule templated Ag nanowires. 8,33,34 To ensure that conductivity is from the nanowires and not random silver precipitates that accidentally bridged the electrodes, control measurements were taken on both a broken device (Fig. 4b) and between unconnected electrodes in the immediate vicinity of the device.…”
Section: Electronic Properties Of Metallic Collagen Nanowiresmentioning
confidence: 99%
“…Long distance hole transfer (HT) in DNA is of outstanding importance; the chemico-physical properties of DNA under oxidative stress, 40? as well as the possibility of using DNA in molecular electronics and molecular computing, [41][42][43][44][45] depend on the efficiency with which an electron hole can move along a strand. Steady state photocleavage analyses and time resolved spectroscopical methods have shown that HT can cover distances up to 200 Å before irreversible oxidation takes place.…”
Section: Coherent Hole Transfer In Dnamentioning
confidence: 99%
“…41 Six methods commonly employed include: (1) Intrinsic anisotropic crystallization of the material, (2) vapor-liquid-solid (VLS) processes from liquid droplet seeds, (3) using a 1D template to direct the formation of 1D structures, (4) using ligands to stabilize certain growing facets leading to anisotropic growth, (5) Templates commonly used include the step edges or V-grooves present on the surfaces of solid substrates, 42,43 the channels and pores of mesoporous materials, 44 solution-born micelles, 45 biological macromolecules such as DNA strains, 46,47 and preexisting nanostructures synthesized using one of the aforementioned methods. 48 Templating against the features of a solid substrate is regularly exploited for the synthesis of nanowires when aspect ratio control is not important or critical.…”
Section: Chapter 2 Hard Template Approach For the Synthesis Of Metalmentioning
confidence: 99%